Correlation between Aspartate Aminotransferase to Platelet Ratio Index Score and the Degree of Esophageal Varices with Liver Cirrhosis - Imam Supriyanto; Suyata Suyata; Syadra Bardiman Rasyad; Fuad Bakry (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTBackground: Esophageal varices is the most common complication in liver cirrhosis. Bleeding varices is a serious complication causing increased mortality rate. In anticipation of those complications, the role of screening test is essential. Endoscopy is the standard method for assessing esophageal varices, but it carries certain risks for patients if it is contraindicated. Moreover, it is an invasive, expensive and uncomfortable procedure. Accordingly, a non-invasive method, aspartat aminotransferase to platelet ratio index (APRI) score, has been developed for evaluating esophageal varices.  Method: An analytic cross-sectional observational study was conducted in patients with liver cirrhosis who underwent endoscopy between March 2011 and August 2012. Data were obtained from medical records of hospitalized patients in Mohammad Hoesin General Hospital. The degree of esophageal varices was assessed based on endoscopic findings and APRI score. Spearman test was performed to analyze the correlation between APRI score and the degree of esophageal varices.Results: There were 55 patients, 30 (54.5%) male and 25 (45.5%) female patients, with a range of age between 15-70 years and a mean value of age of 47.09 ± 12.8. APRI score 0.5 was found in 21.81% subjects, APRI score of 0.5-1.5 was obtained in 41.81% subjects and APRI score 1.5 was noted in 36.36% subjects with a mean value of 2.32 ± 3.92. There was a correlation between APRI score and degree of esophageal varices with p = 0.011 Conclusion: APRI score can indirectly predict esophageal varices in patients with liver cirrhosis. Keywords: APRI score, the degree of esophageal varices, liver cirrhosis